Impact of Unilateral Condyle Fractures on Facial Esthetics Treated by Closed Reduction - Fareed-ud-Din Ahmad Chishti, Saadia Manzar, Ali Abu Bakar, Muhammad Minam Qureshi, Hafiz Muhammad Jawaad Manzoor, Sadia Gull (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Open reduction and internal fixation is gold standard treatment of displaced condylar fractures, yet closed reduction for moderately displaced condylar fractures is used under certain circumstances. Thus, there is possibility that closed reduction may not yield ideal esthetics after treatment. Objective: To measure the mean shortening of ramus length after closed reduction in unilateral condyle fractures. Methodology: This retrospective interventional cohort study was conducted at tertiary care medical facility from August 2013 to November 2018. A total number of 76 participants were enrolled and divided in two groups of 38 patients. Group A were treated by dynamic elastic therapy, whereas, group B patients were treated by maxillomandibular fixation. Results: The average ramus length of group A was 5.75±1.29 mm and group B was 5.76±1.29 mm, thus, there was no significant statistical difference between the two groups (p>0.05). Conclusion: Patients were highly satisfied with their esthetic appearance irrespective of treatment by the two techniques of closed reduction. Keywords: Fractures, Facial asymmetry, Esthetics, Maxillomandibular fixation, Visual Analog Scale.